2020
DOI: 10.1186/s12889-020-09557-w
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and predictors associated with the use of breast cancer screening services among women in 14 low-resource countries

Abstract: Background Breast cancer is one of the leading public health problem globally, especially in low-resource countries (LRCs). Breast cancer screening (BCS) services are an effective strategy for early determining of breast cancer. Hence, it is imperative to understand the utilisation of BCS services and their correlated predictors in LRCs. This study aims to determine the distribution of predictors that significantly influence the utilisation of BCS services among women in LRCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 76 publications
4
25
0
Order By: Relevance
“…The prominent enabling factors include good knowledge of BCS, high education level, increasing age, physician recommendation, etc. This finding is in line with a recent study conducted in 14 low-resource countries where a higher educational level of women was found to be associated with the uptake of BCS [ 47 ]. Women with high education are more aware of health complications and adverse effects of diseases and, therefore, have regular medical check-ups as preventive measures, including BCS services.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prominent enabling factors include good knowledge of BCS, high education level, increasing age, physician recommendation, etc. This finding is in line with a recent study conducted in 14 low-resource countries where a higher educational level of women was found to be associated with the uptake of BCS [ 47 ]. Women with high education are more aware of health complications and adverse effects of diseases and, therefore, have regular medical check-ups as preventive measures, including BCS services.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that women’s household monthly income or good socioeconomic status was a predictor of women undergoing BCS services. This finding is congruent with a study conducted in low and middle-income countries where women in the wealthier quintile were more likely to undergo BCS services than the poor [ 47 ]. Therefore, the conclusion that women with the wealthiest economic status are significantly more likely to utilize BCS services in low-resource countries also aligns with previous findings [ 47 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A meta-analysis conducted by Kassie et al (2020) estimated that the uptake of CCS among women in Ethiopia was 8% and knowledge of CC was significantly associated with the utilisation of CCS. A review of the uptake of BC screening in low-resource countries found that utilisation of BC screening in Asian countries was 19% (Mahumud et al 2020). Factors increasing uptake of BC screening were higher education levels, older age at first birth (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The age for onset of cancer in women in developing countries is decreasing, and the cancers in younger women are more aggressive . Earlier onset could partly be explained by increased awareness, improved breast cancer screening services, and advanced mammography techniques to detect lesions in the breast. , Noninvasive and locally restricted primary tumor is treatable and has a good prognosis. Breast cancer metastasis, common to the lungs, liver, and brain, cripples their functions and leads to mortality .…”
Section: Introductionmentioning
confidence: 99%